Observing atomic layer electrodeposition on single nanocrystals surface by dark field spectroscopy - Shu Hu (Nature Portfolio, 2020)
Underpotential deposition (UPD) is important to modify the surface properties of nanocrystals. Here, the authors show the application of in situ electrochemical dark field spectroscopy in identifying the UPD processes of silver on different facets of gold nanocrystals at the single nanoparticle level.